Effect of Mindfulness-Based Yoga Practices on Anxiety and Attention Level Among High School Children in a Selected High School, Bhubaneswar, Odisha - Puspanjali Senapati; Dhanya V.J.; Rashmi Priya Rath; Bandita Sahoo; Bishnu Priya Mohapatra; Sujata Swain (International Journal of Evidence Based Nursing And Practices, 2023)
Background: In a world filled with endless pressures and expectation, school-aged children often find themselves navigating through a labyrinth of stressors and anxiety. from the moment they wake up their tiny minds are bombarded with worries about exams, social interaction.it is in these moments of chose that the ancient practice of yoga emerges as a gentle beacon of hope, offering solace and tranquility to these young souls. The study main goal is to determine how the MSRT influences student’s levels of Anxiety and Attention. By comparing the pre-post intervention data. The researchers can evaluate whether the yoga-based relaxation technique has a positive impact on these variables. Materials & Methods: There was use of a quasi-experimental study design. Self-structured socio-demographic Performa and standardized tool that is utilizing the STAI Scale and Mindful Attention Awareness Scale which was used to assess the levels of anxiety, and attention respectively. Data from 80 pupils were gathered using a purposive sampling strategy. In selected high schools in Bhubaneswar, Odisha (40 in each intervention and control group). Result: According to the t-test value at p = 0.001, which indicates an extremely high level of statistically significance, The experimental group showed a substantial difference in anxiety and attentiveness pre-and post -testing interval. Conclusion: The outcomes the current investigation suggest that using the Mind sound Resonance Technique has beneficial impact on high school students by enhancing their attention and reducing their anxiety levels. MSRT could be an effective intervention for improving the overall well-being of students in educational setting. However, it’s vital to remember that the study only included a small number of participants. Therefore, to strengthen the validity and applicability of these findings, it is recommended that further research be conducted with a larger or more divers sample. This would allow for a more comprehensive understanding of the potential benefits of MSRT and its generalizability to a wider population.
Keywords: Anxiety; MSRT; attention; high school students; social interaction